Novel inhibitors of RANKL-induced osteoclastogenesis: Design, synthesis, and biological evaluation of 6-(2, 4-difluorophenyl)-3-phenyl-2H-benzo[e][1, 3]oxazine-2, 4(3H)-diones. Issue 15 (1st August 2015) - Lee, Chia-Chung; Liu, Fei-Lan; Chen, Chun-Liang; Chen, Tsung-Chih; Liu, Feng-Cheng; Ahmed Ali, Ahmed Atef; Chang, Deh-Ming; Huang, Hsu-Shan
Graphical abstract: Abstract: A series of novel 6-(2, 4-difluorophenyl)-3-phenyl-2 H -benzo[ e ][1, 3]oxazine-2, 4(3 H )-dione derivatives were synthesized and evaluated for their inhibitory effects on osteoclast activities by using TRAP-staining assay. Among the tested compounds, 3d and 3h exhibited more potent osteoclast-inhibitory activities than the lead compound NDMC503 (a ring-fused structure of NDMC101), as reported in our previous study. Both 3d and 3h exhibited two-fold increase in activity compared to NDMC503. In addition, our biological results indicated that 3d and 3h could suppress RANKL-induced osteoclastogenesis-related marker genes, such as NFATc1, c-fos, TRAP, and cathepsin K . Notably, 3d could significantly attenuate the bone-resorbing activity of osteoclasts in the pit formation assay. Thus, this study might provide a new class of lead structures that warrant further development as potential anti-resorptive agents.